HASIL DESTILASI KERING KAYU DAN NILAI KALOR DARI BEBERAPA JENIS KAYU HUTAN TANAMAN INDUSTRI - Nurmala Hudaya; Hartoyo Hartoyo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Rapid destructive distillation of 20 Industrial Forest Plantation Timber Species was carried out by using a retort equipped with electrical heating system. This retort was also connected to three condensors and two flask to catch and collect the distillate or condensed gas. The retort capacity was about 4 kg of wood.Treatment conditions given in these experiment were maximum heating temperature of 500°C and 5 hours distillation time.The product (charcoal, tar, pyroligneous liquor) of the destructive distillation of wood showed a wide variation in yield or composition depending on the wood species, age and growth location.This experimental condition produces charcoal yield varying from 21,38 - 38,00%, tar from 4.99 - 13.78% and pyroligneous liquor from 44.91 - 157.17%. Pyroligneous liquor product can be used as disinfectant, weed killer and deodorant. Tar product has a good prospect for wood preservative subtance and medicinal.The destructive distillation of wood under these experimental conditions produced brittle and light charcoal. On the contrarary, hard charcoal could be produced from slower pyrolisis process in a commercial scale.Proximate analyses of charcoal obtained from these experiments revealed that the quality IS suitable for both as raw material for commercial activated carbon and fuel.Calorific values of wood ranged from 4285 to 4994 kcal/kg and charcoal from 6746 to 7748 kcal/kg. Based on these calorific values, wood and charcoal of the 20 wood species observed are excellent material to be used as fuel.